Genomic analysis and plant growth-promoting potential of a Serratia marcescens isolated from food - Silva, Cristiane Rodrigues (2022)
A genomic analysis of the potential application of a Serratia marcescens strain in the plant-growth promotion. We performed whole-genome sequencing of Serratia marcescens isolated from a Minas Frescal Cheese. The genomic repertoire revealed a bacterium of agricultural and biotechnological interest. In the plant-growth promotion traits, we highlight genes encoding proteins possibly responsible for the biosynthesis of phytohormone indole acetic acid, organic compounds that act in iron uptake, and the Phosphate solubilization system. Genes encoding for enzymes like the versatile L-asparaginase stimulates the development of seeds and grains and can benefit the food industry due to a mitigation effect on acrylamide and notably, has medical applications as a chemotherapeutic agent or is applicable by its antimicrobial and anti-inflammatory properties. Moreover, functional diversity of genes encoding for resistance to different metals and metabolism of xenobiotics genes can be found in this strain, reinforcing its biotechnological potential. The versatile enzymes that can be produced by S. marcescens benefit the food, pharmaceutical, textile, agronomic, and cosmetic industries. The relevant genetic systems of S. marcescens described here may be used to promote plant growth and health and improve the environment. To the best of our knowledge, this is the first genome sequence report on S. marcescens isolated from cheese, with potential application as promoting plant growth and providing a baseline for future genomic studies on the development of this species.